2015
DOI: 10.1584/jpestics.d14-061
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics of octachlorodipropyl ether photolysis in aqueous solution

Abstract: The photodegradation kinetics of octachlorodipropyl ether (OCDPE) in aqueous solution have been studied under select conditions. The photodegradation rate constants of OCDPE increase with the increases of temperature and pH. The photolysis rates of OCDPE in the investigated water follow the sequence of pure water>impoundment water>pond water>lake water. The photodegradation product of OCDPE is shown to be 2,3,3-trichloroprop-2-en-1-ol. We propose that the OCDPE photolytic pathways consist of dehydrochlorinatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2017
2017

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…The concentration of OCDPE was obtained by gas chromatography (GC) using an Agilent 6890 instrument equipped with a 63 Ni electron capture detector (ECD) while the OCDPE was identified using an Agilent Technologies 5977A mass spectrometer operating in the EI mode at 70 Ev, equipped with a splitless injector (250 °C). The GC settings were the same as those used our previously reported method (Y.-h. Shi et al 2015 ).…”
Section: Methodsmentioning
confidence: 99%
“…The concentration of OCDPE was obtained by gas chromatography (GC) using an Agilent 6890 instrument equipped with a 63 Ni electron capture detector (ECD) while the OCDPE was identified using an Agilent Technologies 5977A mass spectrometer operating in the EI mode at 70 Ev, equipped with a splitless injector (250 °C). The GC settings were the same as those used our previously reported method (Y.-h. Shi et al 2015 ).…”
Section: Methodsmentioning
confidence: 99%
“…However, OCDPE residues still could be detected in agricultural products and environmental samples. OCDPE was still widely used in household insecticides as synergist; thus, it was suggested that the main source of OCDPE in tea maybe the absorption from the combustion of mosquito coils and the use of aerosols [ 13 , 14 ]. Therefore, it is necessary to study the OCDPE residues in soil-plant systems to guarantee human and environmental safety.…”
Section: Introductionmentioning
confidence: 99%